EPISTOLARY LINES: THE TRANSFORMATIVE POWER OF LETTERS IN SAUL BELLOW'S NOVEL «HERZOG» (Scientific journal of the Fergana State University, 2024)
Saul Bellow's novel "Herzog" testifies to the transformative power of letters written by the hero of the work, Moses Herzog. In particular, the character of the hero changes with the help of letters that he writes. A significant place in the narrative of the novel is occupied by the letters of the main character to various personalities. This correspondence becomes for the hero not only a means of dealing with many of his problems, but also a lifeline that helps him in crisis moments of his life.